2020
DOI: 10.2147/opth.s226425
|View full text |Cite
|
Sign up to set email alerts
|

<p>Burden of Illness in Geographic Atrophy: A Study of Vision-Related Quality of Life and Health Care Resource Use</p>

Abstract: Purpose: To gain comprehensive information on the burden of illness due to geographic atrophy (GA). Methods: This cross-sectional study with a retrospective chart review involved patients aged ≥70 years with physician-confirmed bilateral symptomatic GA due to age-related macular degeneration (GA group), as well as patients of similar age with no ophthalmic condition that in the opinion of the investigator affected visual function (non-GA group). Data relating to patients' current disease status and sociodemogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 36 publications
4
29
0
1
Order By: Relevance
“…GA has a substantial effect on an individual’s mobility and independence [ 35 , 49 ]. One of the main reasons for reduced independence for people with GA is its effect on the ability to drive; over half of all people with GA who have a valid driving licence do not feel confident driving during the day and the majority would not drive at night [ 35 ]. In one study, 66.7% of people diagnosed with GA became ineligible to drive within a median time of 1.6 years [ 20 ].…”
Section: A Patient Perspective On Gamentioning
confidence: 99%
See 1 more Smart Citation
“…GA has a substantial effect on an individual’s mobility and independence [ 35 , 49 ]. One of the main reasons for reduced independence for people with GA is its effect on the ability to drive; over half of all people with GA who have a valid driving licence do not feel confident driving during the day and the majority would not drive at night [ 35 ]. In one study, 66.7% of people diagnosed with GA became ineligible to drive within a median time of 1.6 years [ 20 ].…”
Section: A Patient Perspective On Gamentioning
confidence: 99%
“…GA also reduces one’s ability to recognise faces [ 32 , 33 ], and reading speed decreases as the GA lesion increases in size [ 31 , 34 ]. Critically, GA severely impacts a patient’s ability to drive, which limits their freedom to travel, reducing their independence [ 35 ]. Both AMD and GA increase the risk of depression and susceptibility to falls and injuries as a result of poor visual acuity [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients in the GA group had a significantly lower mean (standard deviation [SD]) NEI VFQ-25 composite score than those in the non-GA group (53.1 [19.05] vs 84.5 [6.55] points, respectively; P < 0.001). 22 Geographic atrophy affects multiple aspects of VRQOL and HRQOL. A US cross-sectional qualitative study explored the burden of illness of GA from the perspectives of patients (n = 8), caregivers (n = 6), and eye care professionals (n = 5).…”
Section: Measurement Of Quality Of Life and Reading Function In Gamentioning
confidence: 99%
“…3 In Europe, a retrospective chart review study investigated health-care resource use among patients in the UK, Germany, Ireland, and Canada with bilateral symptomatic GA versus a non-GA control group. 22 The annualized total cost, consisting of direct ophthalmic health-care resource use, was $2115 per patient with GA, mainly driven by diagnostic tests and procedures ($1278 per patient) (Figure 3). The annualized average direct total cost per patient with GA in this study ($2115) was comparable to direct vision-related medical costs reported for patients with neovascular AMD before anti-VEGF agents were approved in the UK ($3742).…”
Section: Economic Burden Direct Costs and Health Care Resource Usementioning
confidence: 99%
“…Reading speed declines as a function of GA lesion size, location, and growth [50, 51], and GA negatively affects patients’ ability to recognize faces [52, 53]. GA also severely impacts patients’ ability to drive, limiting their freedom to travel [54]; 66.7% of patients become ineligible to drive within a median time of 1.6 years from their diagnosis [12]. AMD and GA also affect other aspects of patients’ quality of life, increasing the risk of depression as well as susceptibility to falls and injuries due to poor visual acuity [55, 56].…”
Section: Introductionmentioning
confidence: 99%